Promoting Problem Solving Skills of Secondary School Students in ’Physical Science through Metacognitive Strategies - Uddin, Md Jamal; Agarwal, P.C.; Panda, B.N. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Problem Solving in one of the vital skill of learning Physical Science in 21st Century. In this study, efforts have been made through Descriptive Survey Method to examine the influence of Metacognitive Strategies on Problem Solving Skills of class IX Students in Physical Science. Sample of 180 students from 4 Government Sponsored Co-education Hindi Medium schools of Kolkata city have been selected through simple random sampling. To assess different Metacognitive Strategies related to Planning, Monitoring and Evaluation, Self–developed close ended questionnaire with five-point Likert-Type scale and a competency based test consisting of 20 problems width four options in each from Newton’s Laws of Motion unit have been taken from class IX text book of Physical Science of West Bengal Board of Secondary Education. The reliability and validity of the tool used was found to be 0.82 and 0.9 respectively. Data were analysed using statistical correlation techniques through SPSS. The study reveals that there is a positive correlation between Metacognitive Strategies and Problem Solving Skills in Physical Science. There is need to acquaint students to monitor and self-evaluate their learning while Solving Problems.